2014
DOI: 10.1093/cid/ciu383
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Hepatitis E in Urban Bangladesh Resulting in Maternal and Perinatal Mortality

Abstract: A large outbreak of hepatitis E occurred in urban Bangladesh during 2008–2009, resulting in increased maternal and neonatal mortality in the affected community. Case-patients who took paracetamol during their illness were more likely to die than other case-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 33 publications
(23 reference statements)
7
82
2
Order By: Relevance
“…27 In Bangladesh, patients typically seek care for acute jaundice from informal health-care providers who do not provide laboratory testing. 9,28 In our study, the majority of laboratory-confirmed hepatitis E cases reported monthly household expenditure above the average monthly household expenditure of Bangladeshi families. Among many acute jaundice cases within each cluster, only a few sought care from health-care facilities and paid for the cost of the test.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…27 In Bangladesh, patients typically seek care for acute jaundice from informal health-care providers who do not provide laboratory testing. 9,28 In our study, the majority of laboratory-confirmed hepatitis E cases reported monthly household expenditure above the average monthly household expenditure of Bangladeshi families. Among many acute jaundice cases within each cluster, only a few sought care from health-care facilities and paid for the cost of the test.…”
Section: Discussionmentioning
confidence: 53%
“…16 Residents living in close proximity are likely to share a municipally supplied water source, a wellknown source of exposure for hepatitis E infection. 9,17,18 Though deep tube well water in Dhaka meets WHO drinkingwater standards at extraction points, water supplied at the household level through pipelines does not. 19,20 Water may become contaminated between the extraction point and household taps in the community through leakage in a pipeline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrates that the majority of notified overseas-acquired HEV infections in Australia were in travellers returning from South Asia, namely India, Bangladesh and Nepal. These countries are endemic for HEV, where large water-borne outbreaks occur seasonally (13,148,243,290). Thus, there is a potential risk to blood safety in Australia from donors after their return from such countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causative agent was not identified until 1983 (93). HEV outbreaks continue to occur in many developing countries including Bangladesh, Nepal and Sudan (202,243,244). HEV is considered endemic in many developing countries.…”
Section: Hepatitis E -An Emerging Infectious Diseasementioning
confidence: 99%